Diseño de un sistema de costos para la bloquera “Virgen del Cisne”, provincia de Cotopaxi, parroquia Pastocalle, durante el segundo trimestre del año 2022 - Guilcazo Estrella, Alexandra Nataly (2022)
The current integrative project was developed in the “Virgen del Cisne” block factory, it dedicated to the construction products production and commercialization, such as the block, the factory main problem derives from production costs determination, due to they establish the product selling price, empirically and do not have adequate control them. The aim this integrative project is to design a cost system, what allows identifying the cost elements involved in production, in order to clearly and precisely establish the sale price and get true information for decision making. The applied research type presents a quantitative approach, which it was applied techniques, such as interviews and observation sheets, information, which allowed identifying the appropriate cost system, adapted to the factory needs. The process cost system design made by Excel software, which allows knowing the quantities, equivalent units report, production cost report and production cost status. Through the cost system design, it helps to determine the used costs each process, the product total and real unit cost for an adequate decision making.